Public Debt Dynamics in New Zealand - Melissa Piscetek (New Zealand Government, The Treasury, 2019)
This paper develops a framework to decompose the change in New Zealand's public debt ratio into four component effects: the primary balance, real GDP growth, real interest rates, and exchange rates. We study New Zealand's debt dynamics over three periods: the decade after the Global Financial Crisis (2008 – 2018), the five-year forecasts (2019 – 2023), and the medium-term projections (2024 – 2033). We find asymmetry between the component effects of the debt dynamics on New Zealand's public debt ratio. The primary balance is the larger contributor to the public debt ratio (either positive or negative), while the automatic debt dynamics (the interest-growth differential and exchange rates) are relatively benign.
Keywords: 330; Public debt; debt dynamics; fiscal policy; debt sustainability; fiscal sustainability